Decrease in diatom dominance at lower Si:N ratios alters plankton food webs. (27th June 2020) - Makareviciute-Fichtner, Kriste; Matthiessen, Birte; Lotze, Heike K; Sommer, Ulrich
Abstract: Many coastal oceans experience not only increased loads of nutrients but also changes in the stoichiometry of nutrient supply. Excess supply of nitrogen and stable or decreased supply of silicon lower silicon to nitrogen (Si:N) ratios, which may decrease diatom proportion in phytoplankton. To examine how Si:N ratios affect plankton community composition and food web structure, we performed a mesocosm experiment where we manipulated Si:N ratios and copepod abundance in a Baltic Sea plankton community. In high Si:N treatments, diatoms dominated. Some of them were likely spared from grazing unexpectedly resulting in higher diatom biomass under high copepod grazing. With declining Si:N ratios, dinoflagellates became more abundant under low and picoplankton under high copepod grazing. This altered plankton food web structure: under high Si:N ratios, edible diatoms were directly accessible food for copepods, while under low Si:N ratios, microzooplankton and phago-mixotrophs (mixoplankton) were a more important food source for mesograzers. The response of copepods to changes in the phytoplankton community was complex and copepod density-dependent. We suggest that declining Si:N ratios favor microzoo- and mixoplankton leading to increased complexity of planktonic food webs. Consequences on higher trophic levels will, however, likely be moderated by edibility, nutritional value or toxicity of dominant phytoplankton species.